Capital-constrained loan creation, household stock market participation and monetary policy in a behavioural new Keynesian model - Naira Kotb; Christian R. Proa\~no (International Journal of Finance & Economics, 2022)
In this paper, we incorporate a stock market and a banking sector in a behavioural macro-finance model with heterogenous and boundedly rational expectations. Households' savings are diversified among bank deposits and stock purchases, and banks' lending to firms is subject to capital-related deviation costs. We find that households' participation in the stock market, coupled to the existence of a capital-constrained banking sector affects the transmission of monetary policy to the economy significantly, and that households' deposits act as a critical spill-over channel between the real and the financial sectors. Further, we relate the deviation costs in the banking sector with the degree of pass-through of monetary policy shocks. Last, we investigate the performance of a leaning-against-the-wind monetary policy, which targets asset prices concerning macroeconomic and financial stability.
Keywords: 330; banking; Behavioural macroeconomics; monetary policy; stock markets